PENGEMBANGAN MODUL PRAKTIKUM BERORIENTASI PROBLEM BASED LEARNING PADA ALAT PERAGA TRAINER SISTEM STARTER - Erwin Hamidi; Hasanuddin Hasanuddin; Sugeng Pramudibyo (Universitas Negeri Gorontalo, 2022)
In an effort to realize independent learning for students with the help of learning media, researchers conducted research on the development of problem based learning oriented practicum modules. Learning media can affect the level of students' understanding of learning. This study aims to determine the feasibility of the problem-based learning -oriented practicum module problem-based learning This research is a type of development research using a 4D model (four-D model). The results showed that the problem-based learning was categorized as very feasible. This can be seen from the assessment of media experts obtained 85%, material experts obtained 85%, and responses from students obtained 94%.-oriented module problem-based learning was declared very feasible and received a positive response to be used as a learning medium. Keywords: Module, Problem Based Learning.